The Use of Mind Mapping to Improve Motivation in Learning Vocabulary of Second Grade Students at MTS NW Mispalah Praya - Setianingsih, Tri; Rosihan, Moh; Pardani, Sulastri (JOLLT Journal of Languages and Language Teaching, 2019)
This research was aimed to describe the use of mind mapping technique be able to improving students’motivation.The subject of this study was 37 students at second grade students of MTs. NW Mispalah Praya. In which consist of 25 males and 12 females. It is was classroom action research with one cycle, each cycle of four steps: planning, acting, observing, and reflecting. The data gathering used observation sheet and test and analyzed by using quantitative and qualitative approach. At the result of pre-test was failed where the mean score of pre-test was 65 and class percentage was 52% and the result of the first cycle that the mean score was 70,4 and the class percentage was 100% indicating the target of 70 of the minimum criterion has been achieved, it means that the action was stopped